Studi Literatur: Integrasi Teknologi Informasi Dalam Pelatihan Guru Sebagai Upaya Meningkatkan Kualitas Pembelajaran - Entriza, Aditya Niko; Puspitasari, Fantika Febry (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article examines the integration of technology in teacher training as an effort to enhance the quality of education in the digital era. Employing a literature review approach, the study analyzes various emerging technologies, including Artificial Intelligence (AI), Virtual Reality (VR), and Augmented Reality (AR), and how these technologies are applied in teacher training to support the development of pedagogical competencies. Technology enables personalized training, enhances instructional effectiveness through automated and interactive feedback, and fosters deeper and more immersive learning experiences. The article also explores challenges in technology integration, such as unequal access and limited digital literacy among teachers. Furthermore, microlearning-based training models and online learning platforms emerge as flexible and inclusive solutions. The findings indicate that despite significant challenges, technology can substantially improve the quality of teacher training, leading to more effective and relevant learning, and catalyzing transformation in teaching practices across diverse educational contexts. The article recommends that educational policies provide greater support for the adoption of technology in teacher training to better prepare educators for the demands of the 21st century.